Evolución del bioetanol en Colombia (2017)
This monograph shows the evolution of bioethanol in Colombia, expressing the problems in the social, economic and environmental areas in different geographical areas of the country. Various documents related to the production of biofuels and bioethanol in the country were consulted, the raw materials of plant origin necessary for their process, the change of use of agricultural land to move to energy soils and the geographical areas with agricultural vocation that make Colombia is a promising country to develop industrially bioethanol from various raw materials such as sugarcane.